Effectiveness of structured teaching program on knowledge and practice regarding breast self-examination among college girls in a selected college of Bhilai, Chhattisgarh, India - Tiwari, Anjana; Naik, Mamta (International Journal Of Community Medicine And Public Health, 2018)
Background: Breast self-examination (BSE) is most sensitive and cost effective method to diagnose breast cancer at an early stage. The present study was aimed to assess the effectiveness of structured teaching program on the knowledge and practice regarding breast self-examination among college girls. Methods: A quasi-experimental study was conducted among college girls in the selected college, Mahila Mahavidyalaya, Bhilai from January 2012 to February 2012. Data was collected using a structured knowledge questionnaire and observation checklist and analyzed using both descriptive and inferential statistics in terms of frequency, percentage, mean, standard deviation, student’s t- test, ‘r’ value (Karl Pearson correlation of co-efficient) and chi square test. Results: Among the 30 college girls with 15in experimental group and 15in control group, majority (60%) of girls belongs to the age group of 19-20 years. After intervention, the mean post-test knowledge and practice score of college girls were significantly increased in experimental group (p=0.00). The mean post-test knowledge and practice score of college girls in experimental group was significantly higher than the control group (p=0.00). Moderate correlation was found between post-test knowledge and post-test practice (r=0.47) in experimental group. The post-test knowledge and practice of experimental group were significantly associated with age and area of residence. Conclusions: The present study demonstrated that the structured teaching program was effective in enhancing the knowledge and the practice of college girls regarding breast self-examination. So it is recommended that appropriate health education plan should be prepared for college girls to create awareness and motivate them to perform the BSE.